Improving natural products identification through molecular features-oriented precursor ion selection and targeted MS/MS analysis: a case study of Zhi-Ke-Yang-Yin capsule. Issue 51 (22nd November 2022) - Wang, Hongping; Yin, Qiong; Wang, ZiJian; Peng, Ping; Fan, Chunlan; Zhang, Run; Zhao, Chen; Lin, Zhaozhou
Abstract : Chemical substance identification is an indispensable step in research on therapeutic materials based on traditional Chinese medicine and its formulas. Abstract : Chemical substance identification is an indispensable step in research on therapeutic materials based on traditional Chinese medicine and its formulas. The successful characterization of chemical substances mainly relies on high-quality MS/MS spectra. However, to date, relatively few studies have specifically addressed the issues of improving the acquisition of MS/MS spectra of compounds for characterization. The current auto-MS/MS mode, where the precursor ions are selected depending on their signal intensity, encounters a drawback when the sample contains many overlapping signals, leading to compounds with a lower or much lower abundance missing identification. To solve this problem, a strategy in which molecular features oriented precursor ion selection was followed by targeted MS/MS analysis for structure elucidation was proposed. The precursor ions were selected according to their first and second molecular features, namely m / z and retention time, irrespective of their intensities. By performing targeted MS/MS analysis, the MS/MS spectra of many more compounds of interest can be obtained, leading to an improvement in natural product identification. As an example, the chemical substances in the Zhi-Ke-Yang-Yin extract were analyzed using this strategy, and as a result, 431 ingredients were tentatively characterized, including both known and unknown or new compounds.